Need Analysis to Develop Dynamic Fluid E-Assessment Integrated Critical Thinking for Sustainable Education Assisted Google Sites and Formative - rindi kadir; Emiliannur Emiliannur; Hamdi Hamdi; Dea Stivani Suherman (Journal of Innovative Physics Teaching, 2026)
The development of students’ critical thinking skills in physics learning has not been optimally supported by the assessment practices currently used. In the context of 21st-century education, critical thinking is recognized as a fundamental competency for achieving Sustainable Development Goals (SDGs), particularly Goal 4 on quality education. This study seeks to examine the need for developing assessment tools that integrate critical thinking skills with Education for Sustainable Development (ESD) in physics learning”. This study uses a descriptive approach in Research & Development (R&D) involving 25 grade XI Phase F students. Data collection techniques include critical thinking tests based on Facione indicators, student response questionnaires, and teacher interviews.”The findings reveal that students’ critical thinking skills are generally categorized at a moderate to low level, with the weakest performance observed in the inference indicator. This suggests that students still encounter difficulties in connecting physics concepts with real-world phenomena. However, students demonstrate a relatively good level of sustainability awareness. Therefore, it is necessary to develop electronic assessments integrated with ESD to enhance students’ critical thinking skills and improve the overall quality of physics learning”.